(untitled) (Research, Society and Development, 2025)
A concerted effort has been underway to identify novel solutions that will supplant the use of fossil fuels, the combustion of which has been identified as a primary contributor to greenhouse gas emissions. The objective of this paper is to analyze Mozambican public policies regarding the dissemination of the sugar cane sector and its contribution to the national energy matrix. The analysis revealed that the prominent sugar companies, namely Maragra, Xinavane, Chemba, Marromeu, and Mafambisse, collectively produced 2,737,556 tons of sugar cane during the 2019/2020 harvest season, cultivated across an expanse of 47,351 hectares. Regarding sugarcane production, the country possesses the capacity to yield 766,516 tons of bagasse, which has the potential to generate approximately 331,135 megawatt-hours (MWh) per annum. This would be sufficient to supply 689,864 inhabitants per hour. However, the prevailing public policies in Mozambique’s energy sector currently do not mandate the sale or supply of surplus energy produced by industries to the national electricity grid.